IMPLEMENTASI PENDIDIKAN TERPADU DI SD NEGERI 006 PULAU GADANG KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Nefi Andriani; Zulfan Saam; Sudirman AS (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2020)
This research is aimed tofind out the implementation of integrated education  at SD Negeri 006 Pulau Gadang that covers implementation of curriculum, learning process, scoring, teachers and education staffs and also implementation of islamic school’s culture. The approach used in this researchdescriptive qualitative. Research subject is the headmaster of SD Negeri 006 Pulau Gadang. The used in collecting the data are interview, observation, and documentation. In analizing the data of this research, started with the data reducation, displaying, concluding, and verifying the data.The result of this research is that the implementation of integrated education system  at SD Negeri 006 Pulau Gadang is good and the curriculum used is National Education curriculum and religious curriculum was arranged by Integrated Education Team of Kabupaten Kampar. Integrated education system of Kabupaten Kampar is aimed to create the students to become well attitude human, they have correct aqidah, good attitude, smart brain, strong and healthy body, and also they love the Quran. For general lesson, the teachers add religion value and verses of the Quran appropriate to the learning topic. The implementation of learning process and scoring  has been suitable with the standard of process and standard of scoring based on curriculum used. Many efforts has been done by the headmaster to empower the teachers and education staffs at SD Negeri 006 Pulau Gadang like recruitment, task division, professionalism enhancement, and coaching. Applying the Islamic school’s culture program supports the implementation of integrated education  at SD Negeri 006 Pulau Gadang.